Pengaruh Kompensasi, Komunikasi, dan Kepuasan Kerja Terhadap Kinerja Pegawai KPPN Banjarmasin - Muammar Marwa; Dahniar; Tinik Sugiati (Universitas Lambung Mangkurat, 2019)
This research aims to identify and to analyze the effects of compensation (X1), communication (X2), and job satisfaction (X3) simultaneously and partially on the employees’ performance (Y) of KPPN Banjamasin. This research is explanatory research. The samples in this study used saturated sample including 30 respondents who are implementing the overall employee population of KPPN Banjarmasin. To determine the influence of variables X1, X2, X3 to Y, statistical techniques were used; and multiple linear regression analysis was used to examine the effects of simultaneous significance level using the F test; and t test was used to test the level of significance partially. The data was processed using IBM SPSS version 21 program. The results showed that the variable compensation, communication and job satisfaction simultaneously and partially gave positive effects on the employee’s performance. Among the three independent variables, the highest percentage of 8.2% was communication (X1) compared to the two other variables. This was due to that the employees were basically unable to perform anything in general. Communication is needed in driving a broad strategy direction, including the compensation system and policies of implementing job satisfaction needed to be described into performance expectation, so that it will give positive effects on an employee’s performance.